Variable Morphology of Sacrum in General Population - Motasim Billah, Amir Hamza, Muhammad Ali Anjum, Sarah Yunus, Sabika Hussain, Nadia Majeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the large trilateral bones present at the base of the vertebral column is named as sacrum. The body weight transfers from trunk to pelvis and lower extremities. Different studies considering sacral morphological variations are conducted in the western world. The scope and knowledge of these studies in the eastern world is limited. Different sacral anatomies are reported by the scientists. Objective: The purpose of the study was to investigate and measure thoroughly the variable morphologies of sacrum. Study design: It is an investigational and cross-sectional study facilitated by statistical approach. Material and Methods: The study was conducted on 223 skeleton samples. These samples were preserved in the anatomy department of Mufti Mehmood Teaching Hospital Dera Ismail Khan and Bacha Khan Medical Complex Swabi during the period from October 2021 to June 2022. The human research ethical committee of the hospital approved the study. The vernier caliper was used to measure the correlation parameters of variability. The morphological features were calculated. The study also calculated the sacral variation incidence. The sacra with any kind of bony defects were excluded from the study. Results: The anatomical differences reported in the 223 samples were observed to be 59%. Out of the 223 patients the 81 were females and 142 were males. The five variations were reported in the sacral regions, while two samples have the rare sacral variations. The mean age of the included sample was observed to be 44 years. The age of the people whose sacral samples were included in the study was between 21-72 years. The percentage incidence of accessory auricular faces was observed to be 12.5%. The sacral skewness was observed in 24% cases. The 17% showed the transitional vertebra, while sacral spina bifida occulta was seen in 28% samples. Conclusion: This large scale anatomical study provides information about the apparent changes in the morphology of different sacral variables. This study provides comprehensive data about the different sacral variations. The detailed information about the human sacrum is provided. The apparent identification methods by western medical officers are also considered in this work which may help our medical staff to identify the sacral variations. Keywords: Sacrum variations, Sacrum morphology, Accessory auricular faces, Transitional vertebra and Sacral spina bifida occulta